2019
DOI: 10.1128/iai.00493-19
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Coxiella burnetii in a Lysosome-Like Vacuole Does Not Require Lysosomal Hydrolases

Abstract: Coxiella burnetii is an intracellular bacterium that causes query, or Q fever, a disease that typically manifests as a severe flu-like illness. The initial target of C. burnetii is the alveolar macrophage. Here, it regulates vesicle trafficking pathways and fusion events to establish a large replication vacuole called the Coxiella-containing vacuole (CCV). Similar to a phagolysosome, the CCV has an acidic pH and contains lysosomal hydrolases obtained via fusion with late endocytic vesicles. Lysosomal hydrolase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Lysosomal enzymes such as proteases and cathepsins are most active against their substrates in the pH range 3-5 [64,65] and optimally active at pH 4.5 [64]. While the CCV is known to be proteolytically active [5,6], lysosomal hydrolases are not required for growth [66]. Based on our findings that the CCV is less acidic than lysosomes, the mature CCV may not be optimal for lysosomal enzyme activity.…”
Section: Discussionmentioning
confidence: 81%
“…Lysosomal enzymes such as proteases and cathepsins are most active against their substrates in the pH range 3-5 [64,65] and optimally active at pH 4.5 [64]. While the CCV is known to be proteolytically active [5,6], lysosomal hydrolases are not required for growth [66]. Based on our findings that the CCV is less acidic than lysosomes, the mature CCV may not be optimal for lysosomal enzyme activity.…”
Section: Discussionmentioning
confidence: 81%
“…However, these prior findings are contradicted by Howe et al (2010) who reported that CCV harboring virulent or avirulent variants of C. burnetii mature similarly through the endolysosomal route and reach the phagolysosome stage containing proteolytically active cathepsins. Another study supports the notion that lysosomal hydrolases, including Cts D, are not required for C. burnetii growth or viability in CCV (Miller et al, 2019). Specific antibodies found in chronic Q fever patients likely favor C. burnetii replication in human MDM, because opsonization of bacteria with these antibodies prevented the phagosome conversion.…”
Section: Coxiella Burnetiimentioning
confidence: 53%
“…[9] and Miller et al . [10] with our GNPTAB −/− cells. Despite the absence of GlcNAc‐1‐phosphotransferase, confocal immunofluorescence microscopy showed that the pro‐cathepsin D in the GNPTAB −/− cells colocalized with the lysosomal membrane protein, LAMP1, in enlarged late endosomes/lysosomes, indicating transport of the aspartyl protease to this organelle (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that cathepsin D protein expression was markedly elevated in the GNPTAB À/À HeLa cells. Moreover, we and others noted that these cells accumulate only procathepsin D while failing to convert this single-chain molecule to the two-chain form [8][9][10]. Here, we demonstrate that in the absence of the M-6-P pathway, cathepsin D gene expression in HeLa cells is elevated fivefold at the mRNA level but this upregulation occurs independent of either Transcription Factor EB (TFEB) or Transcription Factor E3 (TFE3), two transcription factors that function as master regulators of lysosomal homeostasis [11].…”
mentioning
confidence: 78%